MAHALABIU: KETAKSAAN MAKNA DALAM BAHASA BANJAR (Mahalabiu: Meaning Ambiguity in Banjar Language) - Yuliati Puspita Sari (Salingka, 2016)
This qualitative descriptive research tries to explore and describe different types of ambiguityin Mahalabiu. (Mahalabiu is a typical joke ini Banjarese society in Kalimantan Selatan withBanjar language as the means. The joke technique uses the ambiguous sentences.)Usingsemantic analysis, the researcher identifies three forms of ambiguity. The three ambiguitiesare phonetic ambiguity, grammatical ambiguity, and lexical ambiguity. Phonetic ambiguityoccurs when words are pronounced too fast that the sounds become blur and unclear. Thedifferent words are heard as one sound. Grammatical ambiguity comes up in syntactic level.Lexical ambiguity is the result of using words that have two or more meaning. The existenceof different types of ambiguity shows that Banjar society has high creativity in playing wordsand sentences that can mislead their speaking partners and become jokes. AbstrakPenelitian kualitatif ini dilakukan untuk menggali dan mendeskripsikan berbagai bentuk ketaksaanyang terdapat dalammahalabiu. Melalui kajian semantik ditemukan bahwa ada tiga bentuk ketaksaanyang terdapat dalammahalabiu.Ketaksaan tersebut ada yang berupa ketaksaan fonetik yang munculakibat kata-kata yang dilafalkan terlalu cepat sehingga bunyinya berbaur, ketaksaan gramatikalyang muncul dalam tataran sintaksis, dan ketaksaan leksikal yang disebabkan oleh adanya katayang bermakna lebih dari satu.Munculnya berbagai bentuk ketaksaan tersebut menunjukkan bahwamasyarakat Banjar memiliki kreativitas tinggi dalam mengolah kata dan membentuk kalimat yangmampu mengecoh jalan pikiran lawan tutur sehingga menjadi bahan candaan.